Public School Performance vis-à-vis Safety and Readiness: An Assessment - Alican Mendez Pandapatan (Universitas Pendidikan Indonesia (UPI), 2024)
Safety and readiness are the primary basis for stakeholders to determine security and for conducive teaching-learning. The study focused on assessing the performances of selected public schools. Five schools have participated in this study. A survey questionnaire was distributed to gather the data. The design used is a descriptive method. Three objectives were specified in this study, and these are identifying the respondents’ demographic profile, rating the level of school performance in terms of safety and readiness, and comparing the significant difference in the school performance with the respondents’ demographic profile. It is revealed in the research that the respondents are diverse when it comes to their age, sex, length of service, field of study, and training attended related to safety. Among the school performance indicators, health protocols are rated high by the respondents. Their response is adaptive to the Covid 19 pandemic. The study also revealed that there is no significant difference in school performance perceived when grouped according to demographic profile, however, the level of training of the respondents influences the perceived performance of their schools which indicates significance. School safety and readiness are implemented through the good leadership of school administrators and sending teachers to training to develop skills and more critical observation in the school performance.